Sikap, Dukungan Manajemen Terhadap Kesehatan Dan Keselamatan Kerja(K3), Penggunaan Alat Pelindung Diri, Dan Dermatitis Akibat Kerja Di PT Elite Prestige Furniture Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Occupational dermatitis is one of the disease that caused by working which manifest with skin anomaly appearance because of working process. Furniture industry is an industry that uses basic commodity and chemistry substances. The aim of this research is to study the Safety and Occupational Health attitude level, management support to Safety and Occupational Health, Self Protecting tools utility in working area, and occupational dermatitis. This research is using cross sectional method. The population and sample are taken from labor force staff production of PT Elite Prestige Furniture. The independent variables of this research were Safety and Occupational Health attitude level, management support to safety and Occupational Health, self protecting tools utility. The dependent variable was occupational dertnatitis. The data was analyzed using qualitative analyzes and quantitative analyzes. The regression analyzes result of Safety and Occupational Health attitude and self protecting tools utility show that there was a significant relationship while the management support shows that there was insignificant relation to occupational dermatitis with coefficient correlation number of 0.847 and p = 0.000 with value of 141.080 R2 = 0.717. The Safety and Occupational Health attitude give relative and effective as 85.67 % and 61.43 %. Connected with Safety and Occupational Health attitude, therefore, some one who has a high K3 knowledge level so the probability of self protecting tools utility is also high enough, that's why the occupational dermatitis can be anticipated. The regression analyzes result and regression coefficient shows that management support variable has no effect to dermatitis. Keywords: attitude-management-protection-equipment-occupational skin disease